THE EFFECT OF LECTURER CERTIFICATION ALLOWANCE AND WORKLOAD ON LECTURER PERFORMANCE WITH ORGANIZATIONAL COMMITMENT AS AN INTERVENING VARIABLE AT THE YOGYAKARTA INSTITUTE OF TECHNOLOGY - Elyta, Erminda Katon; Chasanah, Uswatun (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2024)
This study aims to determine the effect of lecturer certification allowances and workload on performance with organizational commitment as an intervening variable. This research was conducted at the Yogyakarta Institute of Technology with 32 respondents who already have educator certificates or have been certified. The type of research is quantitative with Smart Part Least Square (PLS) analysis tool version 4.0.9.6. Based on the results of the study, it shows that the direct effect of lecturer certification allowances does not have a positive and significant effect on lecturer performance. Workload has a positive and significant effect on lecturer performance. Lecturer certification allowances have a positive and significant effect on organizational commitment. Workload positively and significantly affects organizational commitment. Organizational commitment has no effect on performance. Furthermore, for indirect influences, it shows that organizational commitment is unable to interven the relationship between lecturer certification allowances and performance. Organizational commitment is not able to interven the relationship between workload and lecturer performance at the Yogyakarta Institute of Technology.